To Evaluate the Impact of ICT Tools on Teaching Effectiveness and Student Engagement - ., Aradhana; Bhattacharya, Dr. Shilpi (Journal of Ecohumanism, 2024)
This research article explores the impact of Information and Communication Technology (ICT) tools on teaching effectiveness and student engagement. The study aimed to assess how the integration of digital platforms, multimedia, interactive learning tools, and online resources influences teachers’ instructional practices and students’ motivation, participation, and learning outcomes. A mixed-method approach, combining surveys, classroom observations, and interviews, was employed across multiple schools. The findings indicate that ICT tools enhance teaching efficiency by enabling real-time feedback, personalized learning, and collaborative activities. Additionally, student engagement improved through interactive content, gamified lessons, and access to diverse learning materials. Challenges such as inadequate infrastructure and limited teacher training were also identified. The study concludes that ICT integration is a valuable strategy for improving educational outcomes when supported by adequate resources and pedagogical frameworks.